The potential of a targeted unilateral compound training program to reduce lower limb strength asymmetry and increase performance: a proof-of-concept in basketball - Zhang, Wenfeng; Chen, Xing; Xu, Kun; Xie, Hezhi; Chen, Jiayong; Zhu, Ziwei; Ji, Hongshen; Li, Duanying; Sun, Jian (Frontiers in Physiology, 2024)
Objective This study investigates the efficacy of training methodologies aimed at mitigating asymmetries in lower limb strength and explosiveness among basketball players. Methods Thirty male university basketball athletes were enrolled in this research. Initial assessments were made regarding their physical attributes, strength, and explosiveness. Subsequently, the participants were randomly allocated into two groups: an experimental group (EG, n = 15) and a control group (CG, n = 15). Over 10 weeks, the EG engaged in a unilateral compound training regimen, incorporating resistance training exercises such as split squats, Bulgarian split squats, box step-ups, and single-leg calf raises (non-dominant leg: three sets of six repetitions; dominant leg: one set of six repetitions) and plyometric drills including lunge jumps, single-leg hops with back foot raise, single-leg lateral jumps, and single-leg continuous hopping (non-dominant leg: three sets of 12 repetitions; dominant leg: one set of 12 repetitions). The CG continued with their standard training routine. Assessments of limb asymmetry and athletic performance were conducted before and after the intervention to evaluate changes. Results 1) Body morphology assessments showed limb length and circumference discrepancies of less than 3 cm. The initial average asymmetry percentages in the single-leg countermovement jump (SLCMJ) for jump height, power, and impulse were 15.56%, 12.4%, and 4.48%, respectively. 2) Post-intervention, the EG demonstrated a significant reduction in the asymmetry percentages of SLCMJ height and power (p < 0.01), along with improvements in the isometric mid-thigh pull (IMTP) test metrics (p < 0.05). 3) The EG also showed marked enhancements in the double-leg countermovement jump (CMJ) and standing long jump (SLJ) outcomes compared to the CG (p < 0.01), as well as in squat performance (p < 0.05). Conclusion The 10-week unilateral compound training program effectively reduced the asymmetry in lower limb strength and explosiveness among elite male university basketball players, contributing to increased maximal strength and explosiveness.